Material selection for coal flow breaker plate based on fatigue life analysis using finite element method - Lubis, Asnawi; Hadi, Kiagus Abdul; Akmal, Jamiatul; Badaruddin, Mohammad (Jurnal Polimesin, 2025)
Fatigue failure in the coal flow breaker plate of the CV507 screen at PT. Bukit Asam–Tarahan Port has led to production delays and increased maintenance requirements. This study investigates the optimal material selection for the coal flow breaker plate based on fatigue life under bulk impact loading. The structure, modelled as a fixed vertical plate, was analyzed using the Finite Element Method (FEM) with two material options: ST37 and ST52, each at thicknesses of 15 mm and 20 mm. Static structural and explicit dynamic simulations were performed in ANSYS, using an impact load of 15 kN measured from site conditions. The results indicate that ST52 with a 15 mm thickness experienced the highest von Mises stress (2,223.4 MPa) and deformation (14.41 mm). Increasing the thickness to 20 mm reduced stress to 1,465.4 MPa and deformation to 10.99 mm, extending fatigue life to 8.54 months, making it the most suitable option. These findings provide a basis for selecting materials that enhance durability and minimize downtime in coal processing operations.